Production dynamics and the economic value of sustainable tuna (Thunnus sp.) fisheries management in North Maluku Province, Indonesia - Clara Dwi Ananta; Devi Anggita; Raihan Arrasyid; Defa Safira; Muharomansyah Saputra; Sudirman Adibrata (Yayasan Serumpun Karang Konservasi, 2025)
The tuna fishery is one of the capture fisheries subsectors with high economic value and plays a vital role in supporting the economy of coastal communities in North Maluku Province. IFMA 715, which encompasses the Maluku Sea, the Halmahera Sea, Tomini Bay, and the Seram Sea, is one of Indonesia’s potential tuna-producing regions. This study aims to analyze the production dynamics and economic value of tuna fisheries in North Maluku Province, IFMA 715, as a basis for supporting sustainable fisheries management. This study employs a quantitative approach using descriptive methods based on secondary data from the Ministry of Marine Affairs and Fisheries, scientific publications, and relevant literature. The results showed that tuna production in North Maluku Province fluctuated during 2020–2024, with the highest production recorded in 2021 (54,637.76 tons) and the lowest in 2022 (18,940.87 tons). 2021 at 54,637.76 tons, and the lowest in 2022 at 18,940.87 tons. The economic value of tuna production reached its highest level in 2021 at Rp 1,213,290 million. The dominant tuna species caught were yellowfin tuna (Thunnus albacares) and bigeye tuna (Thunnus obesus) Fluctuations in tuna production and economic value are influenced by oceanographic conditions, fishing seasons, fishing effort, fishing gear, the size of the fishing fleet, market demand, and Illegal, Unreported, and Unregulated Fishing (IUU Fishing) activities. The required management strategies include controlling fishing effort, spatially based management of fishing areas, monitoring minimum catch sizes, and strengthening surveillance of illegal fishing to ensure the sustainability of tuna resources in IFMA 715.